Identifikasi Jamur pada rizofir Tanaman Nenas (Ananas comosus L.) dan Uji Indikasi Antagonisnya terhadap patogen Thielaviopsis Paradoxa di Desa Rimbo Panjang Kecamatan Tambang Kabupaten Kampar - Yetti Elfina S; Fifi Puspita (Universitas Riau, 2008)
The objective of this research was to identify the fungi at pineapple rizoshere and indication of its antagonism to Thielaviopsis paradoxa. It was conducted at laboratory from April to Juli 2006 and sampling method was purposive sampling. The parameters of this research were identification of the rizophere fungi and the ability of rizophere fungi ti inhibit the growth of Thielaviopsis paradoxa. The reasult of this research can be summarized that the pineapple rizosphere fungi identified were: 1). Bispora Sp, 2). Trichocladium Sp, 3). Trichoderma harzianicum, 4). Trichoderma longibrachiatum. Bispora Sp. and Trichocladium Sp. Do not have the ability to inhibit the growth of Thielaviopsis paradoxa, while Trichoderma harzianicum and Trichoderma longibrachiatum have the ability y to inhibit the growth of Thielaviopsis paradoxa.